PUBLIC CONTROL IN THE FIELD OF FIGHT AGAINST CORRUPTION (Scientific journal of the Fergana State University, 2024)
The article highlights insufficient social control over this corruption as one of the factors that create conditions for the commission of corruption crimes. The analysis of the stated definitions shows that there are different approaches to understanding the object of public control.